Farm crime : an international perspective - Donnermeyer, Joseph F. (Routledge, 2025)
A little known and under-appreciated area in criminology is knowledge about the extent, pattern, and costs of crime committed against agriculture. Farm Crime: An International Perspective is the first book to summarize the existing literature from across the globe about agricultural victimization. It demonstrates the vulnerability of farms and farm families to both property and violent crime and how it threatens their livelihood and lifestyles.Written by a pioneer of rural criminology, this book provides both a descriptive synthesis of agricultural victimization and a discussion of various criminological theories applied to its study. Despite the great diversity of farms in different regions of the world and the significant differences between the kinds of crime committed against farms from continent to continent, Farm Crime summarizes common areas of vulnerability. It provides a significant agenda for the future study of agricultural victimization, both in terms of its importance to issues of food security and the safety of farm families around the world.This book is essential reading for green criminologists, rural criminologists, mainstream criminologists, and sociologists alike. It will also be of interest to researchers and policymakers focused on issues of rural development, agricultural policy, and food security.
Keywords: Rural crimes.; Criminology.; elektronické knihy; electronic books